2012
DOI: 10.1016/j.pmrj.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma as a Nonsurgical Treatment Option for Osteonecrosis

Abstract: Avascular necrosis (AVN) is a progressive condition characterized by bone tissue cell death as a result of ischemia, which is most often seen in weight-bearing joints. The traditional treatment of this disease process in the hip includes surgical decompression and joint replacement. This case report describes a novel nonsurgical approach for treating advanced-stage degenerative AVN of the hip with the use of autologous platelet-rich plasma. The patient demonstrated significant functional improvements after thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
(73 reference statements)
0
7
0
2
Order By: Relevance
“…They concluded that an injection of PRP in the sectioned Achilles tendon of rat influences the early phase of tendon healing and results in an ultimately stronger mechanical resistance. These results had a major clinical relevance because most of the clinical researches suggested that PRP is effective in the early period of healing process [60][61][62][63][64][65][66] .…”
Section: Ratmentioning
confidence: 82%
See 2 more Smart Citations
“…They concluded that an injection of PRP in the sectioned Achilles tendon of rat influences the early phase of tendon healing and results in an ultimately stronger mechanical resistance. These results had a major clinical relevance because most of the clinical researches suggested that PRP is effective in the early period of healing process [60][61][62][63][64][65][66] .…”
Section: Ratmentioning
confidence: 82%
“…It has also been shown that due to the presence of leukocytes, PRP grafts are bactericidal, especially against Staphylococcus aureus and Escherichia coli 42 . Most of the clinical trial studies suggested that PRP was a safe method in treating the soft and hard tissue injuries [60][61][62][63][64][65][66] . Contraindications in the use of PRP grafts include septicaemia, thrombocytopaenia (platelet count < 105/µl), platelet dysfunction syndrome, hypofibrinogenemia, history of corticosteroid injection at the treatment site or systemic use of corticosteroid within 2 weeks of the procedure, the routine use of nonsteroidal anti-inflammatory drugs within 48 h of the procedure, recent fever or illness, skin breakdown or rash at site of injection, history of active tumour, cancer or metastatic state, anaemia (Hgb < 10 g/dl), and active infection with Pseudomonas, Enterococcus, or Klebsiella 53,67 .…”
Section: General Concerns and Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, platelet-rich plasma (PRP), an autologous derivative of whole blood that contains a supra-physiological concentration of platelets 29 , promotes axon regeneration and wound healing, enhances bone regeneration 30 and cartilage repair 31 , augments tendon and ligament repair 32 , 33 , cures chronic soft tissue lesions 34 , 35 , and treats chronic femoral osteomyelitis 36 . Furthermore, there have been studies reporting that ONFH could be treated completely with adipose tissue-derived stem cells and PRP in the early stage 37 , with injected PRP as a nonsurgical approach for advanced stage disease 38 , and that a single injection of PRP accelerates surgical angiogenesis in vascular-implanted necrotic bone 39 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PRP can promote re-epithelization of chronic cutaneous wounds [8], enhance bone regeneration [9], augment tendon and ligament repair [10, 11], treat chronic femoral osteomyelitis [12], and prevent glucocorticoid (GC)-induced apoptosis in osteonecrosis of the femoral head (ONFH) [13]. Moreover, the regenerative and anti-inflammatory effects of OA have been widely reported [4, 1416], and IA administration of PRP provides a nonsurgical approach for advanced-stage disease [17]. It is believed that activated platelets secrete high amounts of growth factor (GF) and cytokines, the delivery of which contributes to the major functions of PRP, including promoting proliferation and inhibiting apoptosis of chondrocyte s[1820].…”
Section: Introductionmentioning
confidence: 99%